Service Quality Factors that Influence Patient Satisfaction at Buleleng Regional Hospital - Dwijayanti, Kadek Alvina; Wirajaya, I Wayan Angga; Sukadana, Kadek; Kusuma, Nyoman Yudiana (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The quality of service in the Radiology Department of Buleleng Regional Hospital is determined by several service quality factors: tangible aspects, reliability, responsiveness, assurance, and empathy. This research aimed to observe the service quality factors that affect patient satisfaction and determine which factor is the most dominant and influential in the Radiology Department of Buleleng Regional Hospital. The research uses a quantitative system with a survey approach conducted in April 2024. The study population includes all outpatient patients receiving radiology services at Buleleng Regional Hospital, with a sample size of 30 cooperative outpatients or their families. The collected data were analyzed using SPSS, including validity tests, reliability tests, univariate analysis, and bivariate analysis using Spearman's correlation test. The results show that patient satisfaction in the Radiology Department of Buleleng Regional Hospital is determined by service quality factors: tangible aspects, reliability, responsiveness, assurance, and empathy. The most dominant factor affecting patient satisfaction is assurance, as indicated by a significant value (Sig. (2-tailed)) of 0.000. Since this value is less than 0.05, assurance has the most notable impact among the service quality variables influencing patient satisfaction.